2014
DOI: 10.1111/jce.12584
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Optoacoustic Monitoring of Lesion Formation in Real Time During Radiofrequency Catheter Ablation

Abstract: Deep-tissue 3-dimensional monitoring of RFA lesion generation in real time was demonstrated for the first time in this work. The results suggest the potential of optoacoustic monitoring for providing critical feedback on lesion position and size during radiofrequency catheter ablation, improving safety and efficacy of these treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 23 publications
(40 reference statements)
1
42
0
Order By: Relevance
“…We confirm the spectral signature observed by Dana et al [20], as well as the increase in signal from ablated tissue observed by Pang et al [19]. However, we find that the correlation based imaging proposed in [20] highlights also the artefacts caused by image reconstruction and that the correlation to non-ablated tissue remains high making it difficult at instances to identify lesions from the rest of the tissue.…”
Section: Contribution Of This Worksupporting
confidence: 90%
See 3 more Smart Citations
“…We confirm the spectral signature observed by Dana et al [20], as well as the increase in signal from ablated tissue observed by Pang et al [19]. However, we find that the correlation based imaging proposed in [20] highlights also the artefacts caused by image reconstruction and that the correlation to non-ablated tissue remains high making it difficult at instances to identify lesions from the rest of the tissue.…”
Section: Contribution Of This Worksupporting
confidence: 90%
“…Two groups have previously performed PA imaging of RF ablation lesions on porcine cardiac tissue ex-vivo [19,20]. Pang et al [19] have identified a maximum lesion to nonablated tissue contrast at 780 nm using a 3 MHz transducer.…”
Section: Photoacoustic Imaging For Lesion Progression Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possible application could be volumetric temperature mapping, where photoacoustic imaging methods have been suggested for measuring the temperature at deep locations. [32][33][34][35] Direct thermographic imaging could offer a non-contact alternative technology.…”
Section: (A)]mentioning
confidence: 99%